2019
DOI: 10.18805/ijar.b-3683
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated prevalence of hard tick in large ruminants of coastal areas of South Gujarat, India

Abstract: A total of 2617 large animals (1682 cattle and 935 buffaloes) of coastal districts (Bharuch, Surat, Navsari and Valsad) of South Gujarat were screened for tick infestation. The tick’s prevalence rate was (p less than 0.05) significantly higher in cross-breed (44.81%) as compared to indigenous cattle (22.93%)/ buffaloes (32.26%). Prevalence of Rhipicephalus (Boophilus) microplus, Hyalomma spp., Haemaphysalis spp. and mixed tick infestation was 57.80, 13.05, 20.32 and 8.83%, respectively. Infestation rate in lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…They are mostly prevalent in tropical and subtropical countries, with its status being endemic in India. The prevalence of tick varies, with even reports of incidence more than 50% in some regions of the country (Patel et al, 2019). Ectoparasite populations exposed to costly, toxic environment damaging ectoparasiticides on a regular basis has led to insecticide/acaricide resistance in various agro climatic zones throughout the globe.…”
Section: Introductionmentioning
confidence: 99%
“…They are mostly prevalent in tropical and subtropical countries, with its status being endemic in India. The prevalence of tick varies, with even reports of incidence more than 50% in some regions of the country (Patel et al, 2019). Ectoparasite populations exposed to costly, toxic environment damaging ectoparasiticides on a regular basis has led to insecticide/acaricide resistance in various agro climatic zones throughout the globe.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in Tamil Nadu reported the prevalence of tick infestation in domestic ruminants [18] . Similarly, in cattle and buffaloes tick infestation was recorded in the states of Punjab, Kerala and Gujarat [19][20][21] . In contrast, several workers published reports on ixodid tick infestation in cattle of various Indian states [22][23][24][25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…In buffaloes, a prevalence rate at 73.26% was noted in the present study. Very low prevalence rate was noted in Kerala [20] and a moderately low and high prevalence rate of infestation was noted in Punjab [19] and Gujarat [21] . In sheep and goats, the prevalence of tick infestation was observed in Tamil Nadu state [30] , whereas slightly higher rate was reported in Karnataka state [31] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors associated with tick prevalence on UK farms have been investigated and included large flock sizes, upland farming and the presence of sheep on cattle farms [20]. However, there are country to country variations in the risk factors associated with tick prevalence [14,21] and this needs to be considered when determining future studies on control and prevention measures against ticks. In the UK, the only authorised acaricides for controlling ticks in sheep are deltamethrin, alphacypermethrin pour-on or high-cis cypermethrin and diazinon plunge dips, which afford upto 6, 8 or 12 week of protection against ticks [7].…”
Section: Introductionmentioning
confidence: 99%